Question
upstudy study bank question image url

\( \left. \begin{array} { l } { \int \frac { x + 5 } { \sqrt { 9 - ( x - 3 ) ^ { 2 } } } d x } \\ { \left. \begin{array} { l } { a ^ { 2 } = 9 \quad u ^ { 2 } = ( x - 3 ) ^ { 2 } \quad x = u + 3 } \\ { a = x - 3 } \\ { d u = d x } \end{array} \right. } \\ { = \int \frac { u + 3 + 5 } { \sqrt { a ^ { 2 } - u ^ { 2 } } } d u } \\ { = \int \frac { u + 8 } { \sqrt { a ^ { 2 } - u ^ { 2 } } } d u } \\ { = \int \frac { u } { \sqrt { a ^ { 2 } - u ^ { 2 } } } d u + \int \frac { 8 } { \sqrt { a ^ { 2 } - u ^ { 2 } } } d u } \end{array} \right. \)

Ask by Harmon Chandler. in Puerto Rico
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La integral se resuelve reemplazando \( u = x - 3 \), lo que da: \[ \int \frac{u + 8}{\sqrt{9 - u^2}} \, du = -\sqrt{9 - u^2} + 8 \arcsin\left(\frac{u}{3}\right) + C \] Sustituyendo de vuelta \( u = x - 3 \): \[ -\sqrt{9 - (x - 3)^2} + 8 \arcsin\left(\frac{x - 3}{3}\right) + C \] Donde \( C \) es la constante de integración.

Solution

Queremos evaluar la siguiente integral:   ∫ (x + 5) / √[9 – (x – 3)²] dx Se propone el cambio de variable u = x – 3, lo cual implica:   x = u + 3  y  dx = du. Reemplazamos en la integral:   ∫ [(u + 3) + 5] / √[9 – u²] du = ∫ (u + 8)/√(9 – u²) du Podemos separar la integral en dos términos:   I = ∫ u/√(9 – u²) du + 8∫ 1/√(9 – u²) du A continuación, evaluamos cada una por separado. 1. Para el primer término, ∫ u/√(9 – u²) du:   Hacemos la derivada inversa de la función √(9 – u²). Observa que:   d/du [–√(9 – u²)] = – (1/(2√(9 – u²)))(–2u) = u/√(9 – u²) Por lo tanto:   ∫ u/√(9 – u²) du = –√(9 – u²) + C₁ 2. Para el segundo término, 8∫ 1/√(9 – u²) du:   Recordamos que la integral ∫ du/√(a² – u²) = arcsin(u/a) + C, siendo a² = 9 ⇒ a = 3.   Luego:   ∫ du/√(9 – u²) = arcsin(u/3) + C₂  y multiplicando por 8:   8∫ du/√(9 – u²) = 8·arcsin(u/3) + C₂ Uniendo ambos resultados y considerando que u = x – 3, la solución general de la integral es:   –√[9 – (x – 3)²] + 8·arcsin((x – 3)/3) + C donde C es la constante de integración. Esta es la solución final en español.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Did you know that this integral is related to the geometry of a circle? The expression \( \sqrt{9 - (x - 3)^2} \) describes a semicircle with a radius of 3 centered at (3,0) on the Cartesian plane. When you perform this integral, you’re calculating the area under the curve of that semicircle alongside some added complexity from the linear term \(x + 5\). If you're tackling a challenging integral like this, one common mistake is to mishandle the trigonometric or substitution identities while simplifying. Remember to keep track of your variables! When substituting \(u = x - 3\) ensures you also adjust your limits correctly if specified, and don’t forget to convert \(dx\) to \(du\) accurately. This might seem trivial, but it can significantly alter your results if overlooked!

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy